Crystallinity in PEEK and PEK after mechanical testing and its dependence on strain rate and temperature - Hamdan, S.; Swallowe, G. M. (Wiley, 1996)
This work extends the results of previous workers on the influence of drawing on the crystallinity of PEEK and PEK to test temperatures well above Tg and to strain rates up to 103 s−1. The study thus includes measurement of crystallinity in samples tested in the strain rate regime where large increases in flow stress have previously been noted in these and other polymers. The results are in reasonable agreement with other workers on PEEK and are representative of the behavior of both PEEK and PEK at temperatures up to 200°C and strain rates up to 102 s−1. However at a strain rate of 103 s−1 a dramatic increase in crystallinity and reduction in d-spacing is observed. It is speculated that a change in crystalline morphology induced by the high rate testing may account for the observed changes in spacing, crystallinity, and flow stress